Helmet use behavior and its relation to head injury of road traffic accident in Indonesia (Basic Health Research, 2018) - Lusianawaty Tana; Delima Delima; Nunik Kusumawardani; Lely Indrawati (Health Science Journal of Indonesia, 2021)
Background: Nationally, the prevalence of injuries tends to increase from 7.5% in 2007, 8.2% in 2013, and 9.2% in 2018. The main cause of injuries is motorcycle accidents (40.6%), which most occur on the highway (42.8%). This is a further analysis of Indonesia Basic Health Research (Riskesdas) 2018 data, to assess the role of sociodemography on helmet use behavior and head injuries due to traffic accident. Methods: The 2018 Basic Health Research was a cross-sectional research, based on data from individuals aged 5 years old and above, who analyzed with helmet use behavior and the incidence of head injuries due to traffic accident as dependent variables. The independent variables consist of sociodemographic characteristics, the role of individual in accident, and the impact of the accident. The data were analyzed by bivariate and multivariate, and taking into account the complex sample in 5% confidence level. Results: The results showed that 44.4% from 19122 individuals aged five years old and above had good behavior in using helmets. The determinants of helmet use behavior were age, gender, education, occupation, economic status, location and area of residence (adjusted OR 1.15—4.5; p≤0.02). The result from14.1% of respondents who had a head injuries caused by traffic accidents. The risk of head injuries due to traffic accidents was 1.17 times (95% CI 1.02—1.35; p 0.03) in the unhelmeted group compared to the helmeted group. Conclusion: Helmet use behavior is connected with the reduction of head injuries due to traffic accidents. Counseling and monitoring of helmet use is need to be improved, especially for the youth category. Keywords: head injury, traffic accident, helmet use Abstrak Latar belakang: Secara nasional, prevalensi cedera cenderung meningkat dari 7,5 % pada tahun 2007, 8,2 % pada 2013, dan 9,2 % pada 2018. Penyebab utama dari cedera adalah kecelakaan bermotor (40,6 %), dan kebanyakan terjadi di jalan raya (42,8 %). Ini merupakan analisis lanjut data Riset Kesehatan Dasar (Riskesdas) 2018 untuk menilai peran sosiodemografi terhadap perilaku penggunaan helm dan hubungan perilaku penggunaan helm dengan cedera kepala akibat kecelakaan lalu lintas. Metode: Riskesdas 2018 adalah riset potong lintang. Data individu umur 5 tahun ke atas dianalisis dengan perilaku penggunaan helm dan kejadian cedera kepala akibat kecelakaan lalu lintas sebagai variabel terikat. Variabel bebas terdiri dari karakteristik sosiodemografi, peran individu dalam kecelakaan, dan dampak kecelakaan. Data dianalisis secara bivariat dan multivariat dengan memperhitungkan complex sample dan 5 % tingkat kepercayaan. Hasil: Hasil menunjukkan bahwa 44,4% dari 19.122 individu umur 5 tahun ke atas mempunyai perilaku yang baik dalam menggunakan helm. Determinan perilaku penggunaan helm adalah umur, jenis kelamin, pendidikan, pekerjaan, status ekonomi, lokasi dan area tempat tinggal (adjusted OR 1,15—4,5; p≤0,02). Sejumlah 14,1% individu mengalami cedera kepala akibat kecelakaan lalu lintas. Risiko cedera kepala pada individu yang tidak menggunakan helm sebesar 1,17 kali (95% CI 1,02—1,35; p 0,03) dibandingkan dengan individu yang menggunakan helm. Kesimpulan: Perilaku penggunaan helm berhubungan dengan penurunan cedera kepala akibat kecelakaan lalu lintas. Penyuluhan dan pemantauan penggunaan helm perlu ditingkatkan terutama pada kelompok remaja. Kata kunci: cedera kepala, kecelakaan lalu lintas, penggunaan helm